PENERAPAN ASUHAN KEPERAWATAN PADA LANSIA DENGAN HIPERTENSI MELALUI INTERVENSI ISOMETRIC EXCERCISE DI RT 006/ RW 008 KELURAHAN WARAKAS - Lies Rahmayanti, (2022)
Hypertension is often referred to as the "silent killer". Cases of hypertension are increasing as a result of lack of physical exercise. Therefore, non-pharmacological treatment is needed in the form of light and simple active movements such as isometric exercise. Isometric exercise is a light movement that has no effect on the length or shortness of the muscle if done correctly. The purpose of implementing isometric exercise is to determine the effectiveness of isometric exercise on reducing blood pressure in the elderly. The application of this isometric exercise is applied to two clients, namely the main managed client and the resume client. Isometric exercise is given 3 times a week and carried out for 5 weeks. The results of the implementation of isometric exercise for 5 weeks showed that in the main managed clients there was a change in blood pressure from 150/110 mmHg to 130/90 mmHg, while in resume clients there was a change in blood pressure from 160/110 mmHg to 140/90 mmHg. These results indicate that isometric exercise is effective in helping lower blood pressure. Community nurses are advised to apply isometric exercise as a companion therapy for clients with hypertension.